Strategy for Patent Protection in Crowdfunding: A Case Study in Malaysia - Liang, Lau Keng; Ismail, Norain (Journal of Technology Management and Business, 2022)
Crowdfunding has become the alternative way for many inventors to raise fund for their business. However, online crowdfunding raises some patent issues that relevant to the inventors. Hence, this paper examines the patent protection issues in crowdfunding practices and the strategies to resolve the issues in the context of Malaysia. For that purpose, interviews were conducted with six experts from crowdfunding operators and fundraisers. The findings showed that the largest obstacle perceived was a lack of awareness amongst the users of crowdfunding pertaining to the importance on how to protect the patent and project confidentiality during the crowdfunding process. Most of the project owners do not prioritise patenting their invention before disclosing the information on the crowdfunding platform, this might lead to patent infringement issues. Furthermore, the disclosed invention may not be patentable, and public disclosure also may put them at risk of infringement allegation by a third party. Crowdfunding users also should be more aware of the importance of intellectual property rights before they launch their crowdfunding campaign through an online basis. A proper patent protection strategy is important to protect inventors in crowdfunding practices in Malaysia.